2014
DOI: 10.1021/ie501296t
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Modeling of Mass Transfer and Adsorption in Liquid–Liquid Dispersions. 2. Application to Calcium Naphthenate Precipitation in Oils Containing Mono- and Tetracarboxylic Acids

Abstract: A dynamic multicomponent mass transport model is constructed and solved to determine the interfacial composition and bulk phase concentrations of surfactant mixtures containing a synthetic tetracarboxylic acid (BP10) and decanoic acid (DA) for water droplets dispersed in oil. The transport model employs a molecular mixed monolayer adsorption model that was parametrized by MD simulation and interfacial tension experiments in part 1 [Kovalchuk, K.; Riccardi, E.; Grimes, B. A. Ind. Eng. Chem. Res. 2014, ]. The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…This means that when the two metal ions (Ca 2+ , Mg 2+ ) present in a solution, most likely Ca 2+ will be able to diffuse faster to any available COO -groups, especially for tetracarboxylic acids adsorbed at an oil-water interface where transport dynamics 7,8 should affect the selectivity.…”
Section: Fig 5: Helmholtz Free Energy E Int Curves Of the Metal Imentioning
confidence: 99%
See 1 more Smart Citation
“…This means that when the two metal ions (Ca 2+ , Mg 2+ ) present in a solution, most likely Ca 2+ will be able to diffuse faster to any available COO -groups, especially for tetracarboxylic acids adsorbed at an oil-water interface where transport dynamics 7,8 should affect the selectivity.…”
Section: Fig 5: Helmholtz Free Energy E Int Curves Of the Metal Imentioning
confidence: 99%
“…8, the results presented in the previous sections are schematically summarized in an attempt to explain the specific ion selectivity. It should be noted that the scaling in the figure does not represent the true values and it is made just for clarity of illustration.…”
mentioning
confidence: 99%
“…The results suggested similar behavior of the two TAs as a function of the increasing interfacial concentration, where 50% of the TA molecules are cross-linked when the interfacial coverage is around 70%. The fractional conversion increases nonlinearly with an increase of the surface coverage but does not demonstrate the sigmoidal shape assumed by Kovalchuk et al 12 Thus, the f p (Γ TA ) calculated in this work should be employed in the process model of Kovalchuk et al 12 to properly characterize the cross-linking mechanism in the multiscale framework. Analysis of the intra-and intermolecular cross-linked sites demonstrated that the intramolecular sites are dominating and are increasing linearly with an increase of the surface concentration.…”
Section: ■ Conclusionmentioning
confidence: 71%
“…An important constituent function in this multiscale approach is the fractional conversion [f p (Γ TA )] of TAs to calcium naphthenate precipitates as a function of the interfacial concentration of TAs. Because the functionality of the fractional conversion is not known, Kovalchuk et al 12 assumed f p (Γ TA ) to have a sigmoidal shape.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation